PERAN KEPUASAN DAN KETERIKATAN EMOSIONAL PADA LOYALITAS PELANGGAN (STUDI PADA ANGGOTA PERSEBAYA SELAMANYA) - HUSNA, IRSALINA (Jurnal Ilmu Manajemen (JIM), 2020)
Persebaya is a soccer club from Surabaya which has an Official Merchandise Store named Persebaya Store. Where every purchase at the Persebaya Store, financially helped Persebaya club. In each match, Persebaya must provide maximum performance by winning the match. With the victory, Bonek will feel the satisfaction of the Persebaya club performance and emotional attachment to the Persebaya club increasing to be able to create customer loyalty. The sampling technique used was non-probability sampling with judgmental sampling method and the sample used was 220 respondents. The population in this study was an active member of Persebaya Selamanya who saw the Persebaya match for at least the past month and had made purchases at the Persebaya Store Sutos last month and respondents in this study were aged 19-39 years. Distribution of questionnaires offline using a Likert scale and the analysis used is multiple linear regression analysis. The results showed that satisfaction and emotional attachment significantly influence customer loyalty. Keywords: customer loyalty; emotional attachment; retail; satisfaction; sport